2024
DOI: 10.1007/s11783-024-1812-7
|View full text |Cite
|
Sign up to set email alerts
|

Electronic regulation to achieve efficient anaerobic digestion of organic fraction of municipal solid waste (OFMSW): strategies, challenges and potential solutions

Yongdong Chen,
Hong Wang,
Parisa Ghofrani-Isfahani
et al.

Abstract: Anaerobic digestion (AD) of organic fraction of municipal solid waste (OFMSW) is prone to system breakdown under high organic loading rates (OLRs) condition, which subsequently reduces the efficiency of digestion process and results in substantial economic losses. In this perspective paper, the substances metabolisms, electrons flow, as well as microbial interaction mechanisms within AD process are comprehensively discussed, and the underlying bottleneck that causes inefficient methane production is identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Furthermore, PCoA based on Bray–Curtis dissimilarity of viral communities revealed that the 18 samples collected from 8 food waste treatment plants clustered into two distinct regions ( R 2 = 0.45, P < 0.05) (Figure S2). These findings suggested a significant alteration in viral community composition following AD, aligning with known shifts in bacteria and archaea community compositions during the AD process. ,, PERMANOVA analysis further supported AD processes as an essential predictor of β diversity in viral community composition ( R 2 = 0.23, adjusted P < 0.05). It was necessary to recognize that disparities in dietary habits, sampling times, and geographical locations might contribute to variations in viral communities.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, PCoA based on Bray–Curtis dissimilarity of viral communities revealed that the 18 samples collected from 8 food waste treatment plants clustered into two distinct regions ( R 2 = 0.45, P < 0.05) (Figure S2). These findings suggested a significant alteration in viral community composition following AD, aligning with known shifts in bacteria and archaea community compositions during the AD process. ,, PERMANOVA analysis further supported AD processes as an essential predictor of β diversity in viral community composition ( R 2 = 0.23, adjusted P < 0.05). It was necessary to recognize that disparities in dietary habits, sampling times, and geographical locations might contribute to variations in viral communities.…”
Section: Resultssupporting
confidence: 93%